2015
DOI: 10.1103/physrevb.92.035423
|View full text |Cite
|
Sign up to set email alerts
|

Tunable spin-polaron state in a singly clamped semiconducting carbon nanotube

Abstract: We consider a semiconducting carbon nanotube (CNT) laying on a ferromagnetic insulating substrate with one end depassing the substrate and suspended over a metallic gate. We assume that the polarised substrate induces an exchange interaction acting as a local magnetic field for the electrons in the non-suspended CNT side. Generalizing the approach of I. Snyman and Yu.V. Nazarov [Phys. Rev. Lett. 108, 076805 (2012)] we show that one can generate electrostatically a tunable spin-polarized polaronic state locali… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…[6][7][8] The force sensitivity of the device is then the limiting factor for the sensitivity, and again recent advances showed that it is possible to obtain record force sensing with carbon-nanotube oscillators. 9,10 At the same time nano-mechanical oscillators can be so small that interaction between electronic and mechanical degrees of freedom may lead to new and unexpected phenomena [11][12][13][14][15] like the blockade of the current [16][17][18][19] , cooling [20][21][22] or unusual mechanical response. 23,24 In order to exploit nanomechanical resonators, or to study their properties, detection of mechanical motion is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] The force sensitivity of the device is then the limiting factor for the sensitivity, and again recent advances showed that it is possible to obtain record force sensing with carbon-nanotube oscillators. 9,10 At the same time nano-mechanical oscillators can be so small that interaction between electronic and mechanical degrees of freedom may lead to new and unexpected phenomena [11][12][13][14][15] like the blockade of the current [16][17][18][19] , cooling [20][21][22] or unusual mechanical response. 23,24 In order to exploit nanomechanical resonators, or to study their properties, detection of mechanical motion is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…[33], [34]. It was demonstrated in [35] that the coupling between the spin-carrying and polaronic subsystems results in the appearance of localized quantum states. In [36], the expressions for the charge current both in the shuttling regime and the regime of low-amplitude quantum oscillations were obtained when taking into account the influence of an external magnetic field on tunneling amplitude phase.…”
Section: Introductionmentioning
confidence: 99%
“…e linear dynamic description of nanoelectromechanical systems (NEMS) is well understood when the electromechanical coupling is rather weak [1][2][3][4][5][6][7][8][9]; meanwhile, the existence of the nonlinearities induces too many interesting consequences such as the nonlinear dynamic response in the two-dimensional material membranes, the mechanical bistability in the carbon nanotube (CNT)-based resonator, [10][11][12][13], and unusual mechanical response [8,[14][15][16]. e CNT quantum dot embedded resonators have been widely investigated as ultrasensitive detectors and sensors [17][18][19]; the experimental research group reported higher record sensitivity in mass and force sensing [20,21].…”
Section: Introductionmentioning
confidence: 99%